“People are more afraid of a dementia diagnosis than of death”: The challenges of supporting advance care planning for persons with dementia in community settings - Sussman, Tamara; Tétrault, Bianca (Frontiers in Dementia, 2022)
Improving early uptake of advance care planning (ACP) for persons with dementia and their families requires that staff in community-based settings feel armed and equipped to encourage and support this process. Yet few studies have explored whether staff within non-medical environments feel prepared to support early ACP engagement for persons with early-stage dementia and their families. Our qualitative interpretivist study aimed to fill this gap by facilitating, transcribing and thematically analyzing deliberations from three focus groups with 17 community-based staff. Our findings revealed four key barriers to ACP activation in community settings: (1) the stigma associated with the condition; (2) lack of knowledge about end-of-life concerns for persons with dementia; (3) uncertainties about managing complex family dynamics and (4) worries that opening up conversations about future care may lead to the expression of wishes that could not be actualized (e.g., dying at home). Our findings further revealed that ACP engagement was facilitated when staff expressed confidence in their capacities to gauge readiness, viewed themselves as guides rather than experts and had access to resources to supplement their knowledge. Reflexive training opportunities and access to materials and resources around end-of-life care for persons with dementia, could equip staff in these non-medical settings with the skills to engage in ongoing dialogue about future care issues with persons living with dementia and their families.